Emotional skills and promoting school success in the 3rd cycle : students perception - Campos, Sofia (2017)
Abstract The perceptions about the school play a central role in behavior, performance and learning outcomes. There is evidence that an improvement in emotional skills is associated with a higher school success. The aim of this paper is to establish the relationship between internalizing and externalizing behaviors, emotional skills and academic success of lower secondary education students. In order to promote students social and emotional skills, a pilot study in a School Grouping from the central region of Portugal was carried out. A diagnosis of disruptive behavior (ASEBA) was made and 6 children aged between 12 and 14 years old were identified and followed by 3 focus groups of students, parents, and teachers, respectively. Six students, mostly male, showing signs of externalizing behaviors and academic failure were identified. They didn’t like school and showed no learning motivation. The relationship between parents and teachers was conflictive. All parents had the utmost concern about academic success and teachers showed good practices but without success. This program is seen as a way to improve the educational agents’ action and to help them manage different environments and relationships. The results point out the importance of a systemic intervention program which aims are to improve the social and emotional competences and academic achievement.